Appraising Adaptive Management - Lee, Kai (Conservation Ecology, 1999)
Lee, K. N. 1999. Appraising adaptive management. Conservation Ecology 3(2): 3. https://doi.org/10.5751/ES-00131-030203

Adaptive Management - Bormann, B.T.; Martin, J.R.; Wagner, F.H.; Wood, G.W.; Alegria, J. (Ecological stewardship: a common reference for ecosystem management, 1999)
Wagner
Google-Books-ID: a5vuAAAAMAAJ
Keywords: Conservation of natural resources; Ecology; Ecosystem management; Ecosystem management - United States; Environmental Science; Environmental management; Wildlife

Development as Process: Concepts and Methods for Working with Complexity - Mosse, David; Farrington, John; Rew, Alan (Routledge, 1998)
Process" approaches to economic and social development appear to be more flexible and offer greater prospects of success than traditional "project" methods. Development as Process addresses the questions raised by the different natures of the two approaches. The authors examine development projects through experience in water resources development in India and in organizational learning by a Bangladeshi NGO. Inter-agency contexts are examined in the setting of an aquaculture project in Bangladesh and in the setting of agriculture and natural resources development in Rajisthan, India. Finally, the role of process monitoring is explained in the context of policy reform, with illustrations from forestry in India and land reform in Russia.
Google-Books-ID: baVE8SzJkNMC
Keywords: Demography; Economic Development; Sociology

Whose Reality Counts? Putting the First Last - Chambers, Robert (ITDG Publishing, 1997)
In this sequel to "Rural Development: Putting the last first" Robert Chambers argues that central issues in development have been overlooked, and that many past errors have flowed from domination by those with power.Development professionals now need new approaches and methods forinteracting, learning and knowing. Through analyzing experience - of past mistakes and myths, and of the continuing methodological revolution of PRA (participatory rural appraisal) - the author points towards solutions.In many countries, urban and rural people alike have shown an astonishing ability to express and analyze their local, complex and diverse realities which are often at odds with the top-down realities imposed by professionals. The author argues that personal, professional and institutional change is essential if the realities of the poor are to receive greater recognition. Self-critical awareness and changes in concepts, values, methods and behaviour must be developed to explore the new high ground of participation and empowerment."Whose Reality Counts?" presents a radical challenge to all concernedwith development, whether practitioners, researchers or policy-makers, in all organizations and disciplines, and at all levels from fieldworkers to the heads of agencies. With its thrust of putting the first last it presents a new, exciting and above all practical agenda for future development which cannot be ignored.